Diary of a Wimpy Kid : The Meltdown - Book 13 The meltdown - Kinney, Jeff (New York : Amulet Books, 2018)
When snow closes Greg Heffleys middle school, he and his best friend, Rowley Jefferson, face a fight for survival as warring gangs turn the neighborhood into a wintry battlefield.
Keywords: Diaries -- Juvenile fiction; Snow -- Juvenile fiction; Winter -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Comics & Graphic Novels / General; Junior Fiction